(untitled) (The Review of Diabetic Studies, 2025)
Process innovation in medical clinics has increasingly become a structural prerequisite for facilitating patient treatment stages, supporting reliable clinical transitions, and maintaining continuity across outpatient care pathways. This review analyzes contemporary evidence examining how ambulatory and outpatient clinics design, develop, and refine clinical processes to enable smoother sequential treatment progression—from initial patient intake, clinical assessment, diagnostic evaluation, treatment planning, care delivery, to post-treatment follow-up. Evidence published between 2016 and 2025 highlights the growing shift from fragmented clinic operations toward structured, patient-centered process engineering models supported by workflow sequencing, standardized clinical transitions, and coordinated multidisciplinary hand-over points. Findings indicate that clinics adopting systematic process design frameworks demonstrate improved treatment-stage predictability, reduced waiting time between transitional boundaries, fewer duplicated clinical procedures, higher adherence to treatment plans, fewer transition-related errors, enhanced patient safety, and stronger satisfaction outcomes. The evidence synthesis underscores that effective clinic process development is increasingly supported through manual-digital workflow layering, treatment-stage continuity enablers, and process adaptability readiness aimed at minimizing bottlenecks and interruptions per stage. However, persistent evidence gaps remain in long-term transition continuity metrics, standardized stage-to-patient mapping frameworks, multimodal process integration for chronic outpatient case flows, and knowledge-synchronized process maturity modeling. This review concludes that clinic process innovation must be an evolving, measurable, and patient-adaptive construct foundational to treatment facilitation, service reliability, and outpatient clinical system performance.